2003
DOI: 10.1046/j.1365-2524.2003.00423.x
|View full text |Cite
|
Sign up to set email alerts
|

‘I could have just done with a little more help’: an analysis of women's help-seeking from health visitors in the context of domestic violence

Abstract: Domestic violence is a serious issue that adversely affects large numbers of women and children. Despite having an adverse impact upon health and welfare, women experiencing domestic violence face a number of difficulties seeking help about their situation from statutory health and welfare agencies. The present paper is based upon a study of British health visiting in relation to women experiencing domestic violence. Drawing upon interview data from 16 women who experienced domestic violence and were the mothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
100
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(104 citation statements)
references
References 7 publications
3
100
1
Order By: Relevance
“…Barlow et al's (2005) study showed the importance of health visitors having the skills and willingness to work collaboratively with women who feel unheard, unable or unwilling to trust service providers, along with the service flexibility required to meet different sets of expectations. Peckover (2003) showed that health visitors often lacked understanding or knowledge of available services for domestic violence, so women did not always disclose their experiences. (Hanley 2007;Baldwin and Griffiths, 2009;Edge, 2010Edge, , 2011Almond andLathlean 2011, Wittkowski et al 2011), with health visitors acknowledging a need for more education for these, and many other, areas of practice.…”
Section: Shortcomings In Practicementioning
confidence: 99%
“…Barlow et al's (2005) study showed the importance of health visitors having the skills and willingness to work collaboratively with women who feel unheard, unable or unwilling to trust service providers, along with the service flexibility required to meet different sets of expectations. Peckover (2003) showed that health visitors often lacked understanding or knowledge of available services for domestic violence, so women did not always disclose their experiences. (Hanley 2007;Baldwin and Griffiths, 2009;Edge, 2010Edge, , 2011Almond andLathlean 2011, Wittkowski et al 2011), with health visitors acknowledging a need for more education for these, and many other, areas of practice.…”
Section: Shortcomings In Practicementioning
confidence: 99%
“…Further, women's fear of escalating violence, shame, their economic dependency, loneliness, concern about losing custody of their children, long waiting times, possible police involvement, lack of knowledge regarding appropriate support and protection have been reported as factors affecting the woman's willingness to seek and receive care (Rodriguetz et al, 1996;Yam, 2000;Peckover, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Losing custody of children may be a real concern for women (Dowd et al, 2002;Peckover, 2003). However, IPV is also a great risk factor for child abuse (Augustyn and McAlister Groves, 2005;Hornor, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…We claim that applying rigid ethical regulations may yield data and participants that are highly selected, and, as happened in our study, fewer interviews and less data that was planned. For example, several domestic violence studies indicate that only a small proportion of victims seek help (Bacchus et al, 2003;Garcia-Moreno, 2002;Krug et al, 2002;Peckover, 2003). This means that studying victims of domestic violence who are already in helping systems only manage to 25 reach the tip of the iceberg.…”
Section: Conclusion and Discussionmentioning
confidence: 99%